2015
DOI: 10.1155/2015/959256
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of Hypertension Stages in Two Countries in Sub-Sahara Africa: Factors Associated with Hypertension Stages

Abstract: Studies using the revised hypertension classification are needed to better understand epidemiology of hypertension across full distribution. The sociodemographic, biological, and health behavior characteristics associated with different stages of hypertension in Ghana and South Africa (SA) were studied using global ageing and adult health (SAGE), WAVE 1 dataset. Blood pressure was assessed for a total of 7545 respondents, 2980 from SA and 4565 from Ghana. Hypertension was defined using JNC7 blood pressure clas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
24
6

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 36 publications
11
24
6
Order By: Relevance
“…This supports the notion that hypertension is a silent killer which did not magnificent unless others wise reach to the sever stage. In multivariate analysis family history of hypertension [AOR: 25.0 (11.65 -98.12)] is positively associated with HTN in the studied community which comparable with this studies [15][16][17]. Walking for at least ten minutes continuously every day was negatively associated with hypertension.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This supports the notion that hypertension is a silent killer which did not magnificent unless others wise reach to the sever stage. In multivariate analysis family history of hypertension [AOR: 25.0 (11.65 -98.12)] is positively associated with HTN in the studied community which comparable with this studies [15][16][17]. Walking for at least ten minutes continuously every day was negatively associated with hypertension.…”
Section: Discussionsupporting
confidence: 84%
“…Then the calculated sample size of 330 was proportionally allocated to the selected kebeles. Each study participants were selected and interviewed every two intervals which were determined by statistical formula until the desired sample size was achieved for the respective kebeles [13][14][15][16][17]. In cases where there is more than one eligible individual in the selected household, a lottery method was used where as if there is no eligible person in the selected household the next household was visited accordingly.…”
Section: Study Design and Participantsmentioning
confidence: 99%
“…BP was positively correlated with BMI, stronger for diastolic than systolic BP. Other studies have also demonstrated ageand BMI-related increases in systolic and diastolic BP [31] or both as independent predictors for arterial hypertension [32]. Overall, 30% of prescreened participants were classified as hypertensive, which is similar to the WHO's age-standardized estimate of 29% [1].…”
Section: Pre-diabetic [%]supporting
confidence: 61%
“…In Nigeria, a neighborhoods country, the prevalence of hypertension among adults fluctuated from 2.1% to 47.2% in a sample of 400 participants [8], whereas in Ghana the prevalence of pre-hypertension and hypertension was 30.7% and 42.4%, respectively in a sample of 6,000 participants [9]. In a sample of 1,431 participants aged 18 years or older, the study older [10].…”
mentioning
confidence: 91%